Allergy-like reactions to methylene blue following laparoscopic chromopertubation: A systematic review of the literature. (July 2019) - Akazawa, Munetoshi; Wu, Yi-Hua; Liu, Wei-Min
Abstract: Methylene blue is commonly used as a tracer in sentinel lymph node mapping for many malignant diseases or chromopertubation during gynecologic laparoscopy. In contrast with other blue dyes such as patent blue V or isosulfan blue, methylene blue rarely causes an allergy-like reaction in patients undergoing sentinel lymph node mapping. However, in chromopertubation, some cases of allergy-like reaction to methylene blue have been reported; these comprise two types: an allergic reaction and methemoglobinemia. In this study, a systematic literature review of allergy-like reactions caused by methylene blue dye following laparoscopic chromopertubation was conducted. A search was conducted in PUBMED, Web of Science, and Scopus from inception until June 2018, using the terms: "methylene blue", "complication", "allergic", "hypersensitive", "lung/pulmonary edema", " methemoglobinemia", "anaphylactic shock", "chromopertubation", "pertubation", "laparoscopic", and "laparoscopy". Ultimately, the eligibility criteria were fulfilled by only 12 case reports. Among 13 cases including our case of severe anaphylactic shock after chromopertubation, allergic reactions were diagnosed in four cases, methemoglobinemia in six, and there was no confirmed diagnosis in three cases; the clinical course consisted of skin changes, blue discoloration of body fluids, respiratory failure, and hemodynamic failure, regardless of the underlying diagnoses. Regarding diagnosis, methemoglobinemia was confirmed with co-oximetry (spectrophotometry). First-line therapy included supportive care for both cases of allergic reactions and methemoglobinemia.